The US-China relationship after coronavirus : clues from history (2020)
Coronavirus struck like a flash of lightning that illuminates for an instant distant horizons otherwise obscured. The impact of this pandemic highlights three central realities of world order—and disorder. First and most fundamentally, coronavirus magnifies the underlying structural reality that will be the defining feature of world order and disorder for as far as any eye can see. In what we are coming to recognize as the Great Rivalry, a rising China is seriously threatening to displace a ruling United States from its accustomed position at the top of every pecking order. In twelve of sixteen cases over the last five hundred years, such Thucydidean rivalries ended in war. Second, despite this inevitable and inescapable rivalry, coronavirus also provides a vivid reminder that each nation faces external threats it cannot defeat by itself acting alone. However unnatural, however uncomfortable, each must come to recognize the other as its insufferable but inseparable conjoined twin. As American and Russian Cold Warriors learned painfully as they acquired superpower nuclear arsenals capable of destroying their adversary, neither could survive a nuclear war. To coexist rather than co-destruct, both came to recognize the necessity to constrain their competition.